A Comparative Theoretical Study of the Role of the Public Sector in China and India. Issue 1 (2nd January 2020) - Saratchand, C.
ABSTRACT: The experience of developing countries such as China has many lessons for other developing countries such as India. It also has relevance for any country which seeks to ensure autonomy of national decision-making in an international economy that is often unfavorable for such a stance. The role of the public sector in China is one of the reasons why a characterization of the development trajectory of that country as being neoliberal would be untenable. The paper will carry out a theoretical comparison of the role of the public sector in China and India. After examining the comparative role of the public sector in both countries, the paper seeks to locate the varied experiences of the two countries in the political economy of decision-making of both countries. The paper will conclude with some suggestions for possible future roles of the public sector in both countries.